N‐Benzyl‐4‐((heteroaryl)methyl)benzamides: A New Class of Direct NADH‐Dependent 2‐trans Enoyl–Acyl Carrier Protein Reductase (InhA) Inhibitors with Antitubercular Activity. (2nd March 2016) - Guardia, Ana; Gulten, Gulcin; Fernandez, Raquel; Gómez, Jesus; Wang, Feng; Convery, Maire; Blanco, Delia; Martínez, María; Pérez‐Herrán, Esther; Alonso, Marta; Ortega, Fátima; Rullás, Joaquín; et al.
Abstract: Isoniazid (INH) remains one of the cornerstones of antitubercular chemotherapy for drug‐sensitive strains of M. tuberculosis bacteria. However, the increasing prevalence of multidrug‐resistant (MDR) and extensively drug‐resistant (XDR) strains containing mutations in the KatG enzyme, which is responsible for the activation of INH into its antitubercular form, have rendered this drug of little or no use in many cases of drug‐resistant tuberculosis. Presented herein is a novel family of antitubercular direct NADH‐dependent 2‐ trans enoyl–acyl carrier protein reductase (InhA) inhibitors based on an N ‐benzyl‐4‐((heteroaryl)methyl)benzamide template; unlike INH, these do not require prior activation by KatG. Given their direct InhA target engagement, these compounds should be able to circumvent KatG‐related resistance in the clinic. The lead molecules were shown to be potent inhibitors of InhA and showed activity against M. tuberculosis bacteria. This new family of inhibitors was found to be chemically tractable, as exemplified by the facile synthesis of analogues and the establishment of structure–activity relationships. Furthermore, a co‐crystal structure of the initial hit with the enzyme is disclosed, providing valuable information toward the design of new InhA inhibitors for the treatment of MDR/XDR tuberculosis. Abstract : KatG is out of the picture ! We discovered a novel class of antitubercular compounds that directly target InhA. Unlike isoniazid, these InhA inhibitors do not require prior activation by KatG. We describe our SAR optimization attempts to improve the whole‐cell activity and physicochemical profile of the initial hit. We also report its co‐crystal structure, showing the binding mode within the InhA active site, which will serve as a template for the design of new scaffolds.